2019
DOI: 10.1016/j.heliyon.2019.e01475
|View full text |Cite
|
Sign up to set email alerts
|

Structures, mechanical properties and antibacterial activity of Ag/TiO2 nanocomposite materials synthesized via HVPG technique for coating application

Abstract: In this study, the structures and mechanical properties of the silver-titanium dioxide nanocomposite material were investigated using Atomic Force Microscopy (AFM). These properties include surface roughness, hardness, and reduced Young's modulus. The nanocomposite material was successfully synthesized using the Horizontal Vapor Phase Growth (HVPG) technique which yielded shapes such as nanoparticles, nanospheres, nanorods, triangular nanocomposites, and nanocrystals. Characterization of nanocomposite material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Moreover, the deposition of Au particles on the surface of ZnO NPs, even at a low molar ratio of ZnO/Au (0.2%), significantly improves the photocatalytic antibacterial activity of ZnO [ 147 ]. Furthermore, Ag-TiO 2 nanocomposite demonstrates antibacterial activity against S. aureus biofilms [ 93 , 148 , 149 ]. It was shown that the inclusion of a 2% composite significantly reduced the formation of biofilms on the surface of the composite resin [ 150 ].…”
Section: Metal Oxide Nanocomposites Against Plankton Cells and Biomentioning
confidence: 99%
“…Moreover, the deposition of Au particles on the surface of ZnO NPs, even at a low molar ratio of ZnO/Au (0.2%), significantly improves the photocatalytic antibacterial activity of ZnO [ 147 ]. Furthermore, Ag-TiO 2 nanocomposite demonstrates antibacterial activity against S. aureus biofilms [ 93 , 148 , 149 ]. It was shown that the inclusion of a 2% composite significantly reduced the formation of biofilms on the surface of the composite resin [ 150 ].…”
Section: Metal Oxide Nanocomposites Against Plankton Cells and Biomentioning
confidence: 99%
“…The results show that by changing curing time and growth temperature, different nanomaterials were produced with different shapes, such as Nanoparticles, Nanorods, Triangular Nanomaterials, and Cotton-like Nanomaterials. The results were then evaluated using SEM-EDX to determine the best shape for different applications such as for anti-bacterial [1,21] and elemental composition. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…By changing the parameter, the nanomaterial shape can be obtained. Previous study lead by Muflikhun et al [1] show the variation of nanomaterials synthesis from Ag/TiO 2 . The complete results of the nanomaterial shapes are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…e plate was placed on the inoculated plates and then incubated at 37°C for 16-24 hours. e pour plate technique was used to grow the colonies under three different setups: negative control of only the bacterial suspension and two setups with the nanocomposites of 17.5 gram Ag and 17.5 gram TiO 2 [38][39][40].…”
Section: Besinis Et Al [8]mentioning
confidence: 99%